(untitled) (Bangladesh Heart Journal, 2018)
Introduction: Aspirin, the most widely used platelet function inhibitor extremely effective at blocking the production of thromboxane in platelets, rendering the platelets incapable of functioning normally, and thus preventing thrombosis. The practice of empirically discontinuing aspirin preoperatively should be abandoned because evidence strongly supports continued use of aspirin in patients for secondary prevention of CAD, CVD, or PVD when undergoing surgery. Methods and Materials: This Observational study was conducted at Department of Cardiac Surgery, NICVD, Dhaka, who underwent off pump CABG (OPCAB), divided in two groups, Group A: 24 patients who stopped and Group B: 24 patients who are continuing aspirin throughout the perioperative period. Post operative blood loss, requirement of blood transfusion, post-operative MI, ICU stay, Total hospital stay (days) and early post-operative complication (Stroke, New arrhythmia in ECG, 30 days mortality) were recorded and included in the study. Results: The key finding of the present study is that preoperatively continued aspirin use was not associated with increased risk of post-operative blood loss, blood transfusion requirements and need for re exploration after OPCAB. Conclusions: Preoperative aspirin therapy should be continued till off-pump CABG without interruption. Bangladesh Heart Journal 2018; 33(1) : 16-21